1995
DOI: 10.1002/pros.2990260109
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of plasma hormone levels, nonhormonal factors, and development of benign prostatic hyperplasia

Abstract: We assessed the relation of plasma hormone levels and nonhormonal factors with subsequent occurrence of surgical treatment for benign prostatic hyperplasia (BPH) among participants in the Physicians' Health Study. Frozen plasma samples, collected at the study onset, were available for 320 men who developed surgically treated BPH up to 9 years later and for 320 age-matched controls. Plasma testosterone (T), dihydrotestosterone (DHT), androstenedione, estradiol (E2), and estrone (E1) were measured for each case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 30 publications
2
90
2
Order By: Relevance
“…27,29,31,[33][34][35][36][37][38][39][40][42][43][44][45] When BPH and LUTS were combined, we observed that the BMI was associated with BPH or LUTS (Figure 1, OR ¼ 1.23, 95% CI 1.03-1.48) and the summary OR were similar in population-based casecontrol study, whereas the summary OR in cohort study and hospital-based case-control study showed no association between BMI and BPH/LUTS. Heterogeneity was detected (Po0.05) among all studies and in the subgroup of population-based case-control studies.…”
Section: Bph and Luts Combinedmentioning
confidence: 70%
“…27,29,31,[33][34][35][36][37][38][39][40][42][43][44][45] When BPH and LUTS were combined, we observed that the BMI was associated with BPH or LUTS (Figure 1, OR ¼ 1.23, 95% CI 1.03-1.48) and the summary OR were similar in population-based casecontrol study, whereas the summary OR in cohort study and hospital-based case-control study showed no association between BMI and BPH/LUTS. Heterogeneity was detected (Po0.05) among all studies and in the subgroup of population-based case-control studies.…”
Section: Bph and Luts Combinedmentioning
confidence: 70%
“…[8][9][10][11] Inverse association emerged for both occupational and recreational PA and was consistently found in different strata of selected covariates. The strongest association emerged with occupational or recreational PA in young adulthood (~50% of risk reduction), but some protection was also found for high PA levels at ages 50-59 years (one-third reduction).…”
Section: Discussionmentioning
confidence: 82%
“…The most plausible mechanisms are related to the modulation of endogenous hormones, in particular androgens and estrogens. 9,15,16 Previous studies showed that androgens are involved in the development and maintenance of BPH, as supported by androgen receptor expression in the prostate epithelium. 17 High levels of PA have been reported to lower basal levels of circulating testosterone, which controls prostate growth 17,18 and BPH.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations